An Arabidopsis neutral ceramidase mutant ncer1 accumulates hydroxyceramides and is sensitive to oxidative stress - Li, Jian; Bi, Fang-Cheng; Yin, Jian; Wu, Jian-Xin; Rong, Chan; Wu, Jia-Li; Yao, Nan (Frontiers in Plant Science, 2015)
Ceramidases hydrolyze ceramide into sphingosine and fatty acids and, although ceramidases function as key regulators of sphingolipid homeostasis in mammals, their roles in plants remain largely unknown. Here, we characterized the Arabidopsis thaliana ceramidase AtNCER1, a homolog of human neutral ceramidase. AtNCER1 localizes predominantly on the endoplasmic reticulum. The ncer1 T-DNA insertion mutants had no visible phenotype, but accumulated hydroxyceramides and showed increased sensitivity to oxidative stress induced by methyl viologen. Plants over-expressing AtNCER1 showed increased tolerance to oxidative stress. These data indicate that the Arabidopsis neutral ceramidase affects sphingolipid homeostasis and oxidative stress responses.